LOKALITAS DALAM BAYANG-BAYANG TEMBAWANG ANTOLOGI PUISI PENULIS KALIMANTAN BARAT - Dewi Juliastuty; Khairul Fuad (tuahtalino, 2016)
Tembawang is specific therminology of Dayak people of West Borneo, which contains the local wisdom as a regulation system of Dayak People. The units in tembawang system are reflection of local diversity in West Borneo, The Equator Land. Therefore, the locality to be an object of this research. The title of this research is Locality in Bayang-Bayang Tembawang Antologi Puisi Penulis Kalimantan Barat. The locality means the events or the problem connected to West Borneo, either in the past and present, such as river culture. Description of poetries data applicate to find the specific locality of West Borneo, and then, it analized  through literary anthropology approach. Therefore the specific locality of West Kalimantan implemented in anthology. The spirit of locality increases and to be base on local therminology, tembawang.